2008
DOI: 10.1002/ibd.20383
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formation of advanced oxidation protein products in IBD

Abstract: IBD was associated with enhanced formation of AOPP, which differed between C and UC with respect to the relationship between rAOPP and disease activity, inflammatory and antioxidant response. These differences may reflect divergent ways that oxidative stress develops in CD and UC. The diagnostic power of rAOPP was insufficient for its clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
5
50
0
1
Order By: Relevance
“…In diabetic patients, correlation of IMA with the urinary albumin/ creatinine ratio and plasma creatinine concentration was observed. 32 Thus, IMA has been proposed as a biological marker of myocardial ischemia in suspected cases of acute coronary syndrome. Extracardiac oxidative stress could elevate IMA levels and thereby limit the usefulness of elevated IMA in the detection of cardiac ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In diabetic patients, correlation of IMA with the urinary albumin/ creatinine ratio and plasma creatinine concentration was observed. 32 Thus, IMA has been proposed as a biological marker of myocardial ischemia in suspected cases of acute coronary syndrome. Extracardiac oxidative stress could elevate IMA levels and thereby limit the usefulness of elevated IMA in the detection of cardiac ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Plasma levels of IMA in T2DM is connected with parameters of oxidative processes such as AOPP and thiol groups (SH). 32 The ROC curve has become popular in recent years for evaluating the discriminatory power of tests, methods or parameters, and displays graphically the relationship between sensitivity and specificity over all possible decision values. The ROC curve also allows for comparison of the sensitivity and specificity over a wide range of cut-off points and the selection of the best diagnostic criterion for the test, methods or parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence exists that high-grade OxS has one of the crucial roles in the pathogenesis of disorders/diseases of the vascular system (atherosclerosis, myocardial infarction, stroke, peripheral artery disease), the nervous system (Alzheimer's disease, Parkinson's disease), the liver (cirrhosis, ethanol damage), the skin (dermatoses), the pancreas (diabetes mellitus), metabolic syndrome, obesity, premature ageing, the eyes (age-related macular degeneration, retinopathy), development of some tumors and the GI (inflammatory bowel disease, coeliac disease, etc), etc (Halliwell & Gutterridge, 1999;Stocker & Keaney, 2004;Kals et al, 2006;Stojiljkovic et al, 2007;Krzystek-Korpacka et al, 2008;Tsukahara, 2007;Suzuki et al, 2007;Vincent et al, 2007;Castellani et al, 2008). It has recently reviewed that harmful GI consequences of radiation therapy have OxS-related background (Spyropoulos et al, 2011).…”
Section: Short Survey Of Oxidative Stress-related Pathological Statesmentioning
confidence: 99%
“…Elevated levels of AOPPs are detected in many types of diseases, including osteoporosis (9)(10)(11)(12)(13)(14). Certain studies have demonstrated that oxidative stress leads to increased levels of AOPPs in osteoblastic MC3T3-E1 cells (15,16); AOPPs have been shown to inhibit the proliferation and differentiation of rat osteoblastic cells through NF-κB (17); these data suggest that AOPPs are associated with the progression of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%